Pengaruh Perceived Quality, Brand Image, Kepuasan Konsumen Dan Brand Trust Terhadap Brand Loyalty Produk Kosmetik Merk Wardah - Izzati, Rosyida Rahma, Drs. Wiyadi, M.M., Ph.D, Soepatini, S.E., M.Si., Ph.D (2016)
The purpose of this research is to analyze: 1) influence of perceived quality on brand loyalty, 2) influence brand image on brand loyalty, 3) influence customer satisfaction on brand loyalty and 4) influence brand trust on brand loyalty. Data was collected from 106 respondent who are consumer of Wardah cosmetics in Surakarta and the surrounding area. The method of analysis use multiple linear regression. Based on the test of all instrument variables are valid and reliable. Classical assumption test indicate that the data normally distribute and linier, moreover there are no multicollinearity and heteroschedastisity. The result of this research showed that: 1) perceived quality has positive and significant influence on brand loyalty, 2) brand image has positive and significant influence on brand loyalty, 3) customer satisfaction has positive and significant influence on brand loyalty and 4) brand trust has positive and significant influence on brand loyalty.